1988
DOI: 10.1017/s0950268800054194
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of ‘thermophilic’ campylobacters in sewage and their removal by treatment processes

Abstract: SUMMARYRemoval of thermophilic campylobacters from sewage at three different stages of treatment at a trickling filter sewage works has been assessed. Samples of incoming sewage, primary sedimentation effluent and final effluent were taken daily from 06.00 h to 20.00 h for 5 consecutive days and the numbers of campylobacters determined by using a most probable number method. Each sample was cultured using 2 h pre-enrichment followed by enrichment in Preston broth for 48 h and detection by plating. Over 78 % of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
1
23
0
2
Order By: Relevance
“…Finally, analysis of species and biotype distribution at the sewage plants showed the predominance of C. jejuni biotypes I and II, in agreement with data reported by others (Taylor et al 1983, Carter et al 1987, Arimi et al 1988, Jones et al 1990c, Stampi et al 1992. This is explained by the fact that C. jejuni is the species most frequently detected in man and most frequently responsible for enteritis caused by campylobacters, probably reflecting its best adaptation and diffusion among human beings.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, analysis of species and biotype distribution at the sewage plants showed the predominance of C. jejuni biotypes I and II, in agreement with data reported by others (Taylor et al 1983, Carter et al 1987, Arimi et al 1988, Jones et al 1990c, Stampi et al 1992. This is explained by the fact that C. jejuni is the species most frequently detected in man and most frequently responsible for enteritis caused by campylobacters, probably reflecting its best adaptation and diffusion among human beings.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, Arimi et al (1988) and Höller (1988) have reported that the reduction of campylobacters during the final step of treatment reached levels of 99.6 and 100%, respectively. In this respect, it should be pointed out that the Governador Island sewage plant was working at reduced capacity throughout 1990 due to repairs (Table IV), what may explain the lower rate of Campylobacter elimination obtained at this plant compared to the Penha plant (Table V).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the distribution of sewage sludge to land may be one of the routes by which thermophilic campylobacters reenter the human food chain (3). Previous studies have shown that sewage and sewage sludge, respectively, contain campylobacters in concentrations of 10 2 to 10 5 CFU/100 ml and 10 1 to 10 3 CFU/100 ml, respectively (12,27).…”
mentioning
confidence: 99%
“…They have been isolated from the feces of domestic farm animals, including beef cattle (8,10), dairy cows, and sheep (21). In order to elucidate possible sources of sporadic Campylobacter infection, phenotypic typing methods such as biotyping and serotyping have been applied to Campylobacter isolates from animal and environmental sources, as well as clinical strains (2,10,23). Epidemiological traceback conclusions based on these typing methods are tentative because of the limited discriminatory potential of the techniques.…”
mentioning
confidence: 99%